ISOLASI DAN IDENTIFIKASI GOLONGAN FLAVONOID PADA EKSTRAK ETIL ASETAT DAUN GEDI (Abelmoschus manihot L.) - C. T. Theodora; I W. G. Gunawan; I M. D. Swantara (Jurnal Kimia (Journal of Chemistry), 2019)
The purpose of this experiment was to determine the flavonoid compounds in ethyl acetat extract of gedi leaves (Abelmoschus manihot L.). In this study, the method of extraction was maceration with semipolar solvent (ethyl acetat), flavonoid phytochemical screening, separation and purity test with chromatography and then identification of the compound using FTIR and UV-Vis spectrophotometer with shear reagent method. Analysis of FTIR spectra showed some functional groups such as OH, CH aliphatic, C = O, CO alcohol, C = C aromatic, and CO ether, whereas the analysis with UV-Vis spectra indicated the presence of band I at a wavelength of 409.4 nm and 238.40 nm for band II which is the auron specific wavelength. After the addition of shift reaget, there was a substitutions of OH groups in C-4, C-6 and C-3' and OR at C-4'. The flavonoid compounds contained in ethyl acetate extract of gedi leaf is suggested to be auron, 3',4,6-trihydroxy,4-alkoxy-auron. Keywords: auron, ethyl acetat extract, flavonoids, gedi leaf, isolation